2016
DOI: 10.17126/joralres.2016.033
|View full text |Cite
|
Sign up to set email alerts
|

Radiographic Evaluation of Root Canal Fillings in a Selected Yemeni Population: A Retrospective Study.

Abstract: Aim: To assess the root canal filling quality performed by general dental practitioners in Yemen through radiographic evaluation. Materials and Methods: Four hundred fifty-five digital panoramic radiographs were selected from the archive of the Dental Health Center in Sana'a, Yemen. The final sample consisted of 221 patients, 685 teeth, and 977 root canals. The criteria for overall radiographic adequacy of root canal fillings were defined as the presence of adequate length, density and taper, and absence of ia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
2
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 25 publications
2
2
2
Order By: Relevance
“…22 Obviously, this explains why the poorly quality of root canal fillings and high prevalence of apical periodontitis were associated with molar teeth than those in anterior region among Yemeni population in previous publications. 23,24 These findings are consistent with the results of other authors. 20,25, 26 Bartlett et al,20 indicated that dental schools might have the opinion that students can develop their skills in challenging cases better in general practice rather than the clinical environment offered by dental schools; therefore, they might prefer to provide students with the knowledge of basic principles of these cases only.…”
Section: Discussionsupporting
confidence: 93%
“…22 Obviously, this explains why the poorly quality of root canal fillings and high prevalence of apical periodontitis were associated with molar teeth than those in anterior region among Yemeni population in previous publications. 23,24 These findings are consistent with the results of other authors. 20,25, 26 Bartlett et al,20 indicated that dental schools might have the opinion that students can develop their skills in challenging cases better in general practice rather than the clinical environment offered by dental schools; therefore, they might prefer to provide students with the knowledge of basic principles of these cases only.…”
Section: Discussionsupporting
confidence: 93%
“…Underfilling of root canals in maxillary molars can be explained by their more complex anatomy with narrow and curved root canals and an increased probability of ledge formation compared to maxillary premolars [ 29 ]. Discrepancies between the present results and some previous studies [ 34 , 35 ] might reflect differences in the training and expertise of clinicians, as well as different methodologies of evaluation. Alrahabi [ 34 ] evaluated the root canal treatments done by undergraduate students using periapical images, and Madfa et al [ 35 ] evaluated the root canal treatments done by general dentists using panoramic images.…”
Section: Underfillingcontrasting
confidence: 99%
“…Discrepancies between the present results and some previous studies [ 34 , 35 ] might reflect differences in the training and expertise of clinicians, as well as different methodologies of evaluation. Alrahabi [ 34 ] evaluated the root canal treatments done by undergraduate students using periapical images, and Madfa et al [ 35 ] evaluated the root canal treatments done by general dentists using panoramic images. In the study of Alrahabi, the prevalence of underfilling was less than that of overfilling in maxillary molars.…”
Section: Underfillingcontrasting
confidence: 99%
“…The regular assessment of dental students’ outcomes in endodontics at the preclinical level will help to improve dental education as well as improving the quality of students’ clinical performance [16]. In Yemen, Madfa et al [17] evaluated the quality of RCT performed by general dental practitioners and found that the RCT quality was poor. On the other hand, no previous studies in Yemen has been conducted to evaluate the quality of RCT performed by dental students.…”
Section: Introductionmentioning
confidence: 99%